Desain Aplikasi Pencarian Kontrakan Kota Tarakan Berbasis Mobile Menggunakan Metode Algoritma Djikstra - Evi Marliyani; Moh. Masduki Syahlan; Obert; Gusmana, Roman (STMIK PPKIA Tarakanita Rahmawati, 2019)
Nowadays, searching for rented accommodation in Tarakan city for students, employees, and the general public, in their search currently most still use word of mouth and social media. With this system it will be difficult to find information such as, in the process of searching for the address it also takes a very long time in searching for rented accommodation in Tarakan city usually students, employees, and the general public usually only listen to or know the information conveyed from one community to another so that the information obtained is not accurate. Dijkstra's algorithm is an algorithm for determining routes with short distances. It is assumed that all distances traveled are positive. The idea of ​​this algorithm is based on the fact that each minimum distance has more than one, but in fact there is only one distance to travel. This happens because all distances are positive. According to the results of the analysis obtained by the author in conducting research on, the Dijkstra Algorithm Method is that the method used is still very inefficient in determining the shortest route because this method does not calculate from all existing paths but only calculates the closest node from the starting point and will calculate when the node has branches and will choose the smallest value from the node that has branches.